A parameterised model of multimodal freight transportation for maritime services optimisation. (1st January 2014) - Rios Prado, Rosa; Crespo Pereira, Diego; del Rio Vilas, David; Rego Monteil, Nadia; Garcia del Valle, Alejandro
Multimodal transport has been promoted by several transport commissions initiatives as an alternative to road transport. A key factor for improving its competitiveness is to provide private and public investors with means of evaluating and selecting the most profitable options. This paper presents a parameterisation schema of a freight transport model for the assessment of a multimodal transport service in terms of its internal rate of return (IRR). Parameterisation enables the application of optimisation algorithms to maximise the profitability. Finally, a case study consisting of the evaluation of a new maritime service for the interregional freight transport in Spain is used to verify the proposed parameterisation.